Development of Resonant Density Meter and Its Application in Tailings Backfilling - Xiaozhou Cheng (Advances in Civil Engineering)
To solve the problems of low measurement accuracy, poor safety, and stability of the traditional pipeline liquid density meter, a MIMR-XZ6 pipeline liquid density meter was designed based on the vibration mathematical model of fluid flowing through the pipeline. The pipeline liquid densitometer mainly consisted of a vibration tube for the liquid passing by, a distributed inductance encircled around the inner wall of the vibration tube, a resistor, and a capacitor, respectively, connected to both ends of the inductance, and the inductor, resistor, and capacitor formed the RLC series resonant circuit; an excitation signal source which could generate an alternating current (AC) voltage signal in different frequencies was applied to both ends of the RLC series resonant circuit, and the AC voltage signal was connected to the series branch formed by the inductance and the capacitor to capture the electrical signals. In view of the practical application of this liquid pipe densitometer in tailings backfilling, the installation method of the liquid pipe densitometer is flexible, and the slurry flows in a fluent and stable manner, meeting the measuring requirement of the resonant concentration analyzer. The MIMR-XZ6 pipeline liquid densitometer was used for online detection of ore pulp density, and the precision of this densitometer met the needs of industrial applications.